2003
DOI: 10.1063/1.1571231
|View full text |Cite
|
Sign up to set email alerts
|

Hot isostatic pressing of powder in tube MgB2 wires

Abstract: The critical current density (Jc) of hot isostatic pressed (HIPed) MgB2 wires, measured by d.c. transport and magnetization, is compared with that of similar wires annealed at ambient pressure. The HIPed wires have a higher Jc than the annealed wires, especially at high temperatures and magnetic fields, and higher irreversibility field (Hirr). The HIPed wires are promising for applications, with Jc>106 A/cm2 at 5 K and zero field and >104 A/cm2 at 1.5 T and 26.5 K, and Hirr ~ 17 T at 4 K. The improvement is at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 15 publications
8
109
2
4
Order By: Relevance
“…At higher strain the filament was broken. In this case, the degradation of the critical current and n-values confirms the pre-stress model; the behaviour is similar to that of Nb 3 compared with a bulk sample by Dhallé et al [7] and a HIPed wire by A. Serquis et al [8]. …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…At higher strain the filament was broken. In this case, the degradation of the critical current and n-values confirms the pre-stress model; the behaviour is similar to that of Nb 3 compared with a bulk sample by Dhallé et al [7] and a HIPed wire by A. Serquis et al [8]. …”
Section: Discussionsupporting
confidence: 66%
“…For the high pressure sintered sample at 35 kbar at 950°C for 0.5 hours, the inductive critical current value was ≈ 10 4 A/cm 2 at 3 T, 20 K. Extrapolation of our measurements at 20 K on tape (b) yields similar values. Moreover, it is also possible to make a comparison with the recent data from Serquis et al [8] who prepared wires by the P.I.T. technique and treated them under hot hisostatic pressure (HIP).…”
Section: Effect Of Mg Additionmentioning
confidence: 99%
“…The decrease of T c of a wire under pressure during reaction would then be related to the loss of p xy holes, the decrease of lattice parameters and of c/a ratio (this effect can create dislocation). On the other hand, Serquis indicated that the annealing in isostatic pressure can increase the density of the MgB 2 material, which also produces small grains, and create dislocations [13]. In another article, Serquis showed that an increase of strain (dislocation) in MgB 2 decreases T c [26].…”
Section: Research Resultsmentioning
confidence: 99%
“…Our previous research for doped MgB 2 wires shows that the disadvantages of un-doped MgB 2 can be eliminated by annealing a wire under isostatic pressure (HIP) [10][11][12]. HIP creates dislocations, eliminates voids, produces small grains and small normal area, increases connections between grains, and increases the density and homogeneity of the MgB 2 material [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to accomplish this have invoked the introduction of numerous techniques including chemical doping, [2][3][4][5][6] irradiation, 7 and various thermomechanical processing techniques. 8,9 Chemical doping is a simple and readily scalable technique. Since MgB 2 has a relatively large coherence length and small anisotropy, the fluxoids to be pinned are stringlike and amenable to pinning by inclusions and precipitates in the grains.…”
mentioning
confidence: 99%